1985
DOI: 10.1002/kin.550170806
|View full text |Cite
|
Sign up to set email alerts
|

Direct study of the catalytic decomposition of chlorine and chloromethanes over carbon films

Abstract: The decompositions of chlorine and chloromethanes over pyrolytic carbon surfaces have been studied by modulated beam mass spectrometry in a low-pressure flow reactor between 850-1280 K. Whereas CH,Cl is thoroughly stable, molecular chlorine readily dissociates by a first-order process with an activation energy about a half of its bond energy. The decompositions of CHzClz and CCl, over clean silica surfaces initially display marked autoacceleration associated with the formation of soot on reactor walls and reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Heterogeneous reactions play an important role in the chemistry of chlorinated hydrocarbons, especially in the ini-tiation which is influenced by soot deposition on the walls [8]. We have observed that wall conditions also have an effect on byproduct formation.…”
Section: Benzene 1l-dichloroethanementioning
confidence: 81%
“…Heterogeneous reactions play an important role in the chemistry of chlorinated hydrocarbons, especially in the ini-tiation which is influenced by soot deposition on the walls [8]. We have observed that wall conditions also have an effect on byproduct formation.…”
Section: Benzene 1l-dichloroethanementioning
confidence: 81%
“…At this stage the atmospheric relevance of present results must be limited to the preliminary statement that carbonaceous surfaces are indeed very active for the decomposition of C1,CF to an extent hardly predictable on the basis of its chemical inertness. Several questions remain to be explored, such as : (1) the similarity between the charcoal material used here and the undefined and necessarily variable properties of atmospheric carbon particles, and (2) the synergism or antagonism of other more abundant and reactive, albeit more lightly bound, pollutants. '' Although both aspects certainly deserve further study they can not be expected to be easily answered, since alternatives to present experiments should involve lower temperatures and the addition of NO,, 0, and hydrocarbons better to simulate actual atmospheric conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated of gaseous ZrCl 4 through further chlorination of ZrCl 2 is that on carbon surface at high temperature, the chlorine thermodynamically most feasible. This is suggested to be molecule dissociates into atoms [20] that are highly reactive. kinetically fast.…”
Section: Mechanism Of the Chlorinationmentioning
confidence: 97%